Analisis Literasi STEM Dalam Pengembangan Pendidikan Vokasi: Konsepsi Pada Pendidikan Tinggi Maritim - Iing Mustain (Politeknik Ilmu Pelayaran Semarang, 2020)
Vocational education is a higher education diploma program that prepares students for jobs with certain applied skills to the Associate Expert or Applied Bachelor program. STEM literacy can bridge higher education with competent human resource graduates in the maritime sector that the industry needs because in vocational education through the revitalization program, the industry must collaborate with the needs of the world of work. The research method uses conceptual description analysis on the problem of STEM literacy needs in maritime colleges. STEM literacy includes Science, Technology, Engineering, and Mathematics literacy. Some of the established indicators can use several references from AAAS, ABET, NRC, NCTM, OECD, and ITEA. According to Bloom's taxonomist, the ability level of cadets according to the author can be implemented at levels C4, C5, and C6 for the cognitive domain. The affective domain on attitudes, beliefs, self-esteem, self-confidence, and motivation, and the psychometric domain on actions that indicate motor skills such as in the use of instruments or tools that are precise and accurate.